Enhanced hydrogen generation by water electrolysis employing carbon nano-structure composites. (8th February 2018) - Patel, C.R.P.; Tripathi, Prashant; Vishwakarma, Alok K.; Talat, M.; Soni, Pawan K.; Yadav, T.P.; Srivastava, O.N.
Abstract: The present study describes the hydrogen generation through electrolysis by using graphene-carbon nanotube (GC) nano-composite electrode. Synthesis of GC nano-composites of various compositions utilizing solution admixing approach has been done. Structural, morphological, microstructural and analysis of quality of various carbon nano-composites have been investigated by using XRD, SEM, TEM, Raman and FTIR techniques. To determine the electrochemical catalytic performance of GC composites, these have been used as working electrode (anode) for electrolysis of water in an alkaline medium (1 M NaOH). The results reveal that the GC73 (70 wt% graphene and 30 wt% CNT) nano-composite is an optimum anode material for hydrogen production. The highest hydrogen production rate of 487 l/h-m 2 has been observed for the composite GC 73. Based on Tafel plot and FTIR characterizations, a feasible mechanism for this high hydrogen yield has been put forward. Highlights: We have described the hydrogen generation through electrolysis by using GC nano-composite anode. The GC 73 nano-composite has been found as an optimum anode material. The maximum hydrogen production rate has been found to be 487 l/h-m 2 .